A lithium-deficient composite negative electrode material and preparation method thereof

CN115763774BActive Publication Date: 2025-03-18四川启睿克科技有限公司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211618580.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-15
Publication Date
2025-03-18
Estimated Expiration
2042-12-15

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, metal lithium anode materials have problems such as uneven deposition, high reaction activity and poor structural stability during charging and discharging, resulting in low energy density and poor circulation performance.

Method used

Biomass porous carbon material is used as the framework structure, active groups are introduced and active sites are constructed, and lithium is filled through the self-propagation technology of metal lithium liquid and vacuum adsorption to form a lithium-leading composite negative electrode material.

Benefits of technology

The structural stability of the negative electrode material and the uniform distribution of lithium liquid in lithium-ion batteries are achieved, dendrite growth is reduced, and the energy density and circulation performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115763774B_ABST
    Figure CN115763774B_ABST
Patent Text Reader

Abstract

The invention discloses a lithium-deficient composite negative electrode material and a preparation method thereof, comprising the following steps: carbonizing a biomass carbon material to obtain biomass carbon; graphitizing the biomass carbon at high temperature to obtain a porous graphitized carbon material; introducing polar active groups into the graphitized carbon material, then washing it with deionized water to neutrality, drying it to obtain a mixed carbon material of biomass carbon, and performing dry sheeting on it; coating a metallic lithium liquid on the surface of the mixed carbon material of biomass carbon, and using vacuum infiltration adsorption to completely infiltrate the metallic lithium liquid into the interior of the mixed carbon material; using a polytetrafluoroethylene scraper to perform vacuum scraping to flatten the metallic lithium liquid on the surface, and cooling it to obtain a lithium-deficient composite negative electrode material. The negative electrode material can solve the problems of low energy density and poor structural stability in a long cycle process in a battery system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery negative electrode materials, and in particular to a lithium-deficient composite negative electrode material and a preparation method thereof. Background Art

[0002] In recent years, as the demand for power batteries in terms of energy density and safety has gradually increased, lithium-ion batteries have become a research hotspot for Chinese scientific researchers and research institutions, especially for high-energy-density lithium-ion batteries. -1 ) and extremely negative potential (-3.040V vs standard hydrogen electrode), and finally determined that the use of metallic lithium negative electrode material in the battery system is a better choice. However, there are still a lot of problems in the entire battery system, mainly the following: (i) The unevenness of lithium ions in the electrochemical deposition process leads to the growth of lithium dendrites, and the volume expansion affects the safety of the entire battery system; (ii) The high reactivity of metallic lithium reacts with the electrolyte to generate an unstable solid electrolyte interface film (SEI layer), which will lead to the generation of "dead lithium" and the continuous consumption of electrolyte, affecting the attenuation of battery capacity and cycle stability; (iii) The water and oxygen content requirements of the storage environment of metallic lithium and the battery equipment environment are high, which will require strict control of the water and oxygen content of the entire process to ensure that metallic lithium is not oxidized, limiting the battery assembly environment and the storage and transportation conditions of the materials, and invisibly increasing the cost of the battery. In the current research system, many researchers add excessive lithium sources to the negative electrode to make up for the loss of active lithium during the electrochemical cycle. However, although this operation improves the cycle performance of the battery, it greatly reduces the energy density, which is contrary to the original intention of using metallic lithium as the negative electrode material. At the same time, if a lithium metal negative electrode that matches the capacity of the positive electrode material is used, the thickness of the lithium metal is too thin and the mechanical properties are too poor to complete the battery assembly problem and ensure the material stability during the electrochemical cycle. Therefore, many researchers attach lithium metal to a copper current collector to support lithium metal sheets; at this time, the interface impedance between lithium metal and copper current collector, the high reactivity of lithium metal itself, and the uneven lithium deposition sites have not been solved.

[0003] In order to solve a series of problems in the charging and discharging process of metallic lithium, scientific researchers have conducted a lot of research and modified metallic lithium negative electrode materials from many aspects to achieve a certain degree of improvement, including: regulating electrolyte additives, using solid electrolyte membranes, modifying current collectors, and coating protective films on the surface of metallic lithium. So far, no way has been found to overcome the above problems. Although the existing research work has modified the metallic lithium negative electrode to improve the growth of lithium dendrites, volume expansion, and the formation of "dead lithium" to a certain extent, it still cannot meet the current high energy density battery in terms of safety performance and electrochemical cycle performance. In addition, there is still no better way to avoid oxidation in the air for the high reactivity of metallic lithium. At the same time, in the battery system, the positive electrode intermediates penetrate the diaphragm into the impurities on the surface of the negative electrode material, which will lead to the loss of active positive electrode active materials and the blockage of the surface of the metallic lithium negative electrode. At present, this problem has not been well solved. At the same time, when using thin lithium strips or lithium sheets as negative electrodes, their mechanical strength is not enough to support the expansion of the system during long cycles. In the soft pack battery system, it is more likely to "break the belt", thereby reducing the overall capacity of the battery. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a lithium-poor composite negative electrode material and a preparation method thereof, using biomass porous carbon material as a framework structure, introducing active groups and constructing active sites, and filling the metal lithium liquid by self-propagating technology and vacuum adsorption, and finally forming a lithium-poor composite negative electrode material. In the process of preparing porous carbon materials, the lithium filling amount is controlled by the combination of carbon materials with different pore sizes, the sintering temperature, and the adjustment of the pressure during the pressing of the carbon base material. The structural stability of the entire negative electrode material during the charge and discharge process is stabilized by the three-dimensional carbon skeleton, and the introduced active groups and active sites are conducive to the self-propagating adsorption of lithium liquid. At the same time, the molten metal lithium liquid is introduced into the gap of the carbon skeleton material by vacuum adsorption, which reduces the amount of excess lithium, and finally forms a low-cost, dendrite-free lithium-poor composite negative electrode material. It is beneficial to solve the problems of low energy density and poor structural stability during long cycles in battery systems.

[0005] In order to achieve the above technical effects, the present invention provides the following technical solutions:

[0006] A method for preparing a lithium-deficient composite negative electrode material comprises the following steps: (1) carbonizing a biomass carbon material to obtain biomass carbon; (2) graphitizing the biomass carbon at high temperature to obtain a porous graphitized carbon material; (3) introducing polar active groups into the graphitized carbon material, then washing it with deionized water until it is neutral, drying it to obtain a mixed carbon material of biomass carbon, and performing dry sheeting on it; (4) coating a metallic lithium liquid on the surface of the mixed carbon material of biomass carbon, and using vacuum infiltration adsorption to completely infiltrate the metallic lithium liquid into the interior of the mixed carbon material; and simultaneously using a polytetrafluoroethylene scraper for vacuum scraping to flatten the metallic lithium liquid on the surface, and cooling it to obtain a lithium-deficient composite negative electrode material.

[0007] The amount of metallic lithium liquid used is determined by calculating the porosity of the material after dry film preparation.

[0008] A further technical solution is that the biomass carbon material is selected from any one or more of bamboo, natural wood, straw, corn cob, meat, wool, pig skin, silkworm feces, and bacteria.

[0009] A further technical solution is that the carbonization in step (1) is specifically carbonized under an inert gas at 300-600°C for 2-10h, and the carbonization temperature is 300-450°C.

[0010] A further technical solution is that the temperature of high temperature graphitization in step (2) is 1000-3000°C.

[0011] A further technical solution is that the polar active group in step (3) is selected from one or more of sulfonic acid group, phosphoric acid group, phosphite group, carboxylic acid group, phenol group and hydroxyl group.

[0012] A further technical solution is that the drying temperature in step (3) is 60-120° C., the drying time is 10-24 h, and the pressure of dry tableting is 100-300 MPa.

[0013] A further technical solution is that the vacuum permeation adsorption in step (4) is carried out at a temperature of 180-300°C.

[0014] A further technical solution is that the cooling in step (4) is first cooled to 60-80°C and kept warm for 1-12 hours, and then cooled to room temperature.

[0015] The present invention also provides a lithium-deficient composite negative electrode material, which is prepared by the above-mentioned preparation method.

[0016] Compared with the prior art, the present invention has the following beneficial effects: the present invention adopts biomass porous carbon material as the framework structure, introduces active groups and constructs active sites, and fills the metal lithium liquid by self-propagating technology and vacuum adsorption, and finally forms a lithium-poor composite negative electrode material. In the process of preparing porous carbon materials, the lithium filling amount is controlled by the compounding of carbon materials with different pore sizes, the sintering temperature, and the adjustment of the pressure during the pressing of the carbon base material. The three-dimensional carbon skeleton stabilizes the structural stability of the entire negative electrode material during the charging and discharging process. The introduced active groups and active sites are conducive to the self-propagating adsorption of lithium liquid. At the same time, the molten metal lithium liquid is introduced into the gap of the carbon skeleton material by vacuum adsorption, which reduces the amount of excess lithium, and finally forms a low-cost, dendrite-free lithium-poor composite negative electrode material. It is beneficial to solve the problems of low energy density and poor structural stability during long cycles in battery systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The figure is a comparison chart of the electrochemical cycle performance of the embodiment of the present invention and the comparative example. DETAILED DESCRIPTION

[0018] The present invention is further described below by way of examples, which are for illustrative purposes only and do not limit the scope of the present invention. The test methods in the following examples without specifying specific conditions are usually carried out under conventional conditions.

[0019] Comparative Example 1

[0020] Pure metal lithium sheet is used as negative electrode material, and LiNi 0.8 Co 0.1 Mn 0.1 The O2 positive electrode sheet was assembled into a 2032 button cell using EC:DEC:DMC=1:1:1 as the electrolyte, and then the electrochemical performance was tested at a charge and discharge rate of 0.2C. The performance test results are shown in Table 1.

[0021] Comparative Example 2

[0022] Pure graphite is used as the negative electrode material, and LiNi 0.8 Co 0.1 Mn 0.1 The O2 positive electrode sheet was assembled into a 2032 button cell using EC:DEC:DMC=1:1:1 as the electrolyte, and then the electrochemical performance was tested at a charge and discharge rate of 0.2C. The performance test results are shown in Table 1.

[0023] Embodiment 1

[0024] First, bamboo was selected as the biomass material, and carbonized under inert gas at 400℃ for 5h to obtain porous biomass carbon; then, it was graphitized at 1800℃ for 10h to obtain porous graphitized carbon material, and concentrated sulfuric acid was added to introduce sulfonic acid active groups, and then filtered, washed, and dried to obtain biomass mixed carbon material with sulfonic acid groups; then, dry tableting was performed, and the pressure was controlled at 200MPa; then, the metallic lithium liquid was spread on the surface of the carbon material by self-propagating adsorption and vacuum adsorption, and finally, a polytetrafluoroethylene scraper was used for vacuum coating to flatten the metallic lithium liquid on the surface, and then it was cooled to 60-80℃ and kept warm for 8h to obtain a lithium-poor composite negative electrode material. The button battery negative electrode sheet was obtained by a slicing machine and compared with LiNi 0.8 Co 0.1 Mn 0.1 The O2 positive electrode sheet was assembled into a 2032 button cell using EC:DEC:DMC=1:1:1 as the electrolyte, and then the electrochemical performance was tested at a charge and discharge rate of 0.2C. The performance test results are shown in Table 1.

[0025] Embodiment 2

[0026] First, natural wood was selected as the biomass material, and carbonized under inert gas at 400℃ for 5h to obtain porous biomass carbon; then, graphitization treatment was performed at 2000℃ for 10h to obtain porous graphitized carbon material, and concentrated sulfuric acid was added to introduce sulfonic acid active groups, and then filtered, washed, and dried to obtain biomass mixed carbon material with sulfonic acid groups; then, dry tableting was performed, and the pressure was controlled at 200MPa; then, the metallic lithium liquid was spread on the surface of the carbon material by self-propagating adsorption and vacuum adsorption, and finally, a polytetrafluoroethylene scraper was used for vacuum coating to flatten the metallic lithium liquid on the surface, and then cooled to 60-80℃ and kept warm for 8h to obtain a lithium-poor composite negative electrode material. The button battery negative electrode sheet was obtained by a slicer and compared with LiNi 0.8 Co 0.1 Mn 0.1 The O2 positive electrode sheet was assembled into a 2032 button cell using EC:DEC:DMC=1:1:1 as the electrolyte, and then the electrochemical performance was tested at a charge and discharge rate of 0.2C. The performance test results are shown in Table 1.

[0027] Embodiment 3

[0028] First, corn cobs were selected as biomass materials, and carbonized at 350℃ inert gas for 5h to obtain porous biomass carbon; then, graphitization treatment was performed at 2000℃ for 10h to obtain porous graphitized carbon materials, and concentrated sulfuric acid was added to introduce sulfonic acid active groups, and then filtered, washed, and dried to obtain biomass mixed carbon materials with sulfonic acid groups; then, dry tableting was performed, and the pressure was controlled at 200MPa; then, the metallic lithium liquid was spread on the surface of the carbon material by self-propagating adsorption and vacuum adsorption, and finally, a polytetrafluoroethylene scraper was used for vacuum coating to flatten the metallic lithium liquid on the surface, and then cooled to 60-80℃ and kept warm for 8h to obtain a lithium-poor composite negative electrode material. The button battery negative electrode sheet was obtained by a slicing machine and compared with LiNi 0.8 Co 0.1 Mn 0.1 The O2 positive electrode sheet was assembled into a 2032 button cell using EC:DEC:DMC=1:1:1 as the electrolyte, and then the electrochemical performance was tested at a charge and discharge rate of 0.2C. The performance test results are shown in Table 1.

[0029] Embodiment 4

[0030] First, silkworm manure was selected as the biomass material, and it was carbonized at 400℃ in an inert gas for 5h to obtain porous biomass carbon; then it was graphitized at 1800℃ for 10h to obtain porous graphitized carbon material, potassium hydroxide was added to introduce hydroxyl polar active groups, and the biomass mixed carbon material with hydroxyl groups was obtained by filtration, washing and drying; then dry pressing was performed, and the pressure was controlled at 200MPa; then the metallic lithium liquid was spread on the surface of the carbon material by self-propagating adsorption and vacuum adsorption, and finally a polytetrafluoroethylene scraper was used for vacuum coating to flatten the metallic lithium liquid on the surface, and then it was cooled to 60-80℃ and kept warm for 8h to obtain a lithium-poor composite negative electrode material. The button battery negative electrode sheet was obtained by a slicing machine and compared with LiNi 0.8 Co 0.1 Mn 0.1 The O2 positive electrode sheet was assembled into a 2032 button cell using EC:DEC:DMC=1:1:1 as the electrolyte, and then the electrochemical performance was tested at a charge and discharge rate of 0.2C. The performance test results are shown in Table 1.

[0031] Embodiment 5

[0032] First, succulents were selected as biomass materials, and carbonized under inert gas at 350℃ for 6h to obtain porous biomass carbon; then, graphitization treatment was performed at 2000℃ for 10h to obtain porous graphitized carbon materials, potassium hydroxide was added to introduce hydroxyl polar active groups, and filtration, washing, and drying were performed to obtain biomass mixed carbon materials with hydroxyl groups; then, dry tableting was performed, and the pressure was controlled at 200MPa; then, the metallic lithium liquid was spread on the surface of the carbon material by self-propagating adsorption and vacuum adsorption, and finally, a polytetrafluoroethylene scraper was used for vacuum coating to flatten the metallic lithium liquid on the surface, and then cooled to 60-80℃ and kept warm for 8h to obtain a lithium-poor composite negative electrode material. The button battery negative electrode sheet was obtained by a slicing machine and compared with LiNi 0.8 Co 0.1 Mn 0.1 The O2 positive electrode sheet was assembled into a 2032 button cell using EC:DEC:DMC=1:1:1 as the electrolyte, and then the electrochemical performance was tested at a charge and discharge rate of 0.2C. The performance test results are shown in Table 1.

[0033] Table 1 Test data of embodiments and comparative examples

[0034] sample Number of cycles (circles) Capacity retention rate (%) Embodiment 1 200 80 Embodiment 2 200 85.6 Embodiment 3 200 98.54 Embodiment 4 200 91.7 Embodiment 5 200 93.5 Comparative Example 1 200 7.5

[0035] Figure 1 The electrochemical cycle performance comparison diagram of Comparative Example 1, Example 3 and Example 5 is given. Figure 1 From the electrochemical cycle performance diagram, it can be clearly seen that the modified sample shows a significant improvement in electrochemical cycle performance. Its capacity retention rate is as high as 98.54% after 200 cycles at a charge and discharge rate of 0.2C. However, the capacity retention rate of the pure metal lithium electrode is only 7.5% after 200 cycles. This can be mainly attributed to the following two points: (1) After high-temperature treatment, the corn cob obtains a three-dimensional negative electrode material with uniform pores, which enhances the structural stability of the material; (2) The ultra-thin pure lithium negative electrode sheet is difficult to support volume changes during long cycles; (3) The three-dimensional framework structure allows lithium to be deposited in different regions, reducing the local current density and thus inhibiting the growth of lithium dendrites.

[0036] Although the present invention is described herein with reference to the illustrative embodiments of the present invention, the above embodiments are only preferred embodiments of the present invention, and the embodiments of the present invention are not limited to the above embodiments. It should be understood that those skilled in the art can design many other modifications and embodiments, which will fall within the scope and spirit of the principles disclosed in this application.

Claims

1. A method for preparing a lithium-deficient composite negative electrode material, characterized in that: The method comprises the following steps: (1) carbonizing a biomass carbon material to obtain biomass carbon; (2) graphitizing the biomass carbon at high temperature to obtain a porous graphitized carbon material; (3) introducing polar active groups into the graphitized carbon material, then washing it with deionized water until it is neutral, drying it to obtain a mixed carbon material of biomass carbon, and performing dry sheeting on it; (4) coating a metallic lithium liquid on the surface of the mixed carbon material of biomass carbon, and using vacuum infiltration adsorption to completely infiltrate the metallic lithium liquid into the interior of the mixed carbon material; and simultaneously using a polytetrafluoroethylene scraper to perform vacuum scraping to flatten the metallic lithium liquid on the surface, and cooling it to obtain a lithium-poor composite negative electrode material.

2. The method for preparing a lithium-deficient composite negative electrode material according to claim 1, characterized in that: The biomass carbon material is selected from any one or more of bamboo, natural wood, straw, corn cob, meat, wool, pig skin, silkworm feces, and bacteria.

3. The method for preparing a lithium-deficient composite negative electrode material according to claim 1, characterized in that: The carbonization in step (1) is specifically carried out at 300-600 o C for 2-10h under inert gas.

4. The method for preparing a lithium-deficient composite negative electrode material according to claim 1, characterized in that: The temperature of high temperature graphitization in step (2) is 1000-3000 o C.

5. The method for preparing a lithium-deficient composite negative electrode material according to claim 1, characterized in that: The polar active group in step (3) is selected from one or more of sulfonic acid group, phosphoric acid group, phosphite group, carboxylic acid group, phenol group and hydroxyl group.

6. The method for preparing a lithium-deficient composite negative electrode material according to claim 1, characterized in that: The drying temperature in step (3) is 60-120 o C, the drying time is 10-24h, and the pressure of dry tableting is 100-300MPa.

7. The method for preparing a lithium-deficient composite negative electrode material according to claim 1, characterized in that: In step (4), vacuum permeation adsorption is carried out at 180-300 o Carry out at temperature C.

8. The method for preparing a lithium-deficient composite negative electrode material according to claim 1, characterized in that: The cooling step (4) is to first cool to 60-80 o C for 1-12 h, then cool to room temperature.

9. A lithium-deficient composite negative electrode material, characterized in that: The compound is prepared by the preparation method described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Three-dimensional self-supported lithium-loving carrier-packaged metal lithium composite negative electrode and preparation method thereof

    CN107799736A

  • Metal lithium negative electrode for in-situ construction of multifunctional biomimetic membrane and preparation method of metal lithium negative electrode

    CN112542564A